TGF-β1 Drives Inflammatory Th Cell But Not Treg Cell Compartment Upon Allergen Exposure - Musiol, Stephanie; Alessandrini, Francesca; Jakwerth, Constanze A.; Chaker, Adam M.; Schneider, Evelyn; Guerth, Ferdinand; Schnautz, Benjamin; Grosch, Johanna; Ghiordanescu, Ileana; Ullmann, Julia T.; Kau, Josephine; Plaschke, Mirjam; et al. (Frontiers in Immunology, 2022)
TGF-β1 is known to have a pro-inflammatory impact by inducing Th9 and Th17 cells, while it also induces anti-inflammatory Treg cells (Tregs). In the context of allergic airway inflammation (AAI) its dual role can be of critical importance in influencing the outcome of the disease. Here we demonstrate that TGF-β is a major player in AAI by driving effector T cells, while Tregs differentiate independently. Induction of experimental AAI and airway hyperreactivity in a mouse model with inducible genetic ablation of the gene encoding for TGFβ-receptor 2 (Tgfbr2) on CD4+T cells significantly reduced the disease phenotype. Further, it blocked the induction of pro-inflammatory T cell frequencies (Th2, Th9, Th17), but increased Treg cells. To translate these findings into a human clinically relevant context, Th2, Th9 and Treg cells were quantified both locally in induced sputum and systemically in blood of allergic rhinitis and asthma patients with or without allergen-specific immunotherapy (AIT). Natural allergen exposure induced local and systemic Th2, Th9 cell and reduced Tregs, while therapeutic allergen exposure by AIT suppressed Th2 and Th9 cell frequencies along with TGF- and IL-9 secretion. Altogether, these findings support that neutralization of TGF-β represents a viable therapeutic option in allergy and asthma, not posing the risk of immune dysregulation by impacting Tregs.